2020
DOI: 10.1097/j.pain.0000000000001833
|View full text |Cite
|
Sign up to set email alerts
|

Parent cognitive, behavioural, and affective factors and their relation to child pain and functioning in pediatric chronic pain: a systematic review and meta-analysis

Abstract: Previous studies have demonstrated that parental cognitive, behavioral, and emotional factors are related to child functioning in children and adolescents with chronic pain. This is particularly important to understand how to potentially enhance the efficacy of psychological interventions for children by incorporating interventions targeting parents. We conducted a systematic review and meta-analysis to identify the specific parent factors that have been examined in the literature and to quantify the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 125 publications
2
56
0
1
Order By: Relevance
“… 10 , 16 , 38 In contrast, parent factors have been consistently related to outcomes associated with other types of pediatric chronic pain. 60 In general, more research is needed to explore the relationships between a range of parent and family factors and pediatric CPSP. In particular, future research should examine parent behaviors and emotional functioning, the parent–child dyadic relationship, and global family functioning at baseline and over time to better understand possible influences on CPSP.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“… 10 , 16 , 38 In contrast, parent factors have been consistently related to outcomes associated with other types of pediatric chronic pain. 60 In general, more research is needed to explore the relationships between a range of parent and family factors and pediatric CPSP. In particular, future research should examine parent behaviors and emotional functioning, the parent–child dyadic relationship, and global family functioning at baseline and over time to better understand possible influences on CPSP.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…Parents play an important role in children's chronic pain experience. The impact of parenting behaviors on the functioning of youth with chronic pain is well-established, 16 and research suggests parents' mental health and physical health are also related to children's chronic pain outcomes. 10 , 12 , 19 , 26 , 32 , 42 , 47 However, adverse childhood experiences (ACEs) among parents of youth with chronic pain have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“… 33 , 34 , 36 , 46 , 50 , 55 , 58 Thus, parent ACEs may contribute to chronic pain in youth, especially given their association with parent factors (eg, mental and physical health) that are implicated in pediatric chronic pain. 4 , 14 , 16 , 26 , 42 , 46 …”
Section: Introductionmentioning
confidence: 99%
“…In addition, while parent diagnostic uncertainty may influence the child’s response to their pain, it is also important to consider how parent diagnostic uncertainty influences the parents’ own response to and cognitions about their child’s pain. A large body of research has shown that parent cognitions, particularly catastrophizing about the child’s pain and resultant protective behaviors, are associated with poor child functioning [ 13 , 14 ]. Of particular relevance to diagnostic uncertainty is a study that found that parents who told a distress (versus resilience) narrative, characterized by more negative affect and an unresolved orientation toward the child’s diagnosis of chronic pain, reported higher levels of catastrophizing about their child’s pain (helplessness subscale) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%